New Experimental Dependence of Machining - Vasilko, Karol (Manufacturing Technology Journal, 2014)
During the application of recent relationships between cutting conditions and results of machining there occur unevenesses, which can lead to incorrect choice of cutting conditions in concrete conditions of machining of engineering parts. Equations used in practice and on the base of wide experimental analysis to optimise their shape are being analysed in the paper. It concerns the evaluation of chip compression, machined surface microgeometry and cutting tools durability.
Keywords: machining; tool durability; cutting conditions; machined surface quality